The WHO FCTC and global governance: effects and implications for future global public health instruments - McInerney, Thomas F (Tob Control, 2019)
INTRODUCTION: This article analyses experience with the WHO Framework Convention on Tobacco Control (WHO FCTC) in the context of global governance. It examines ways in which the WHO FCTC has been addressed by international institutions, particularly within the UN system at the international and national levels. It seeks to understand the extent to which the WHO FCTC as an international legal obligation has contributed to its integration in the strategies, policies and programmes of UN system organisations. METHODS: The article examines documentation reflecting global governance responses to tobacco control since the Convention’s entry into force in 2005. It also considers discussions with officials involved in the design and management of various UN initiatives. Finally, it draws on the findings of the Expert Group on the Impact Assessment of the WHO FCTC. CONCLUSIONS: The influence of the WHO FCTC in global governance can be at least partially attributed to its status as an international legal obligation. While tobacco control would have likely been a priority in international public health even in the absence of the WHO FCTC, the importance of tobacco control has been relatively greater as a result of the treaty. In assessing the potential utility of any future global public health instrument, it is important to consider the need to mobilise action by other global governance institutions and ensure that the chosen instrument will be capable of stimulating such action.